The Impact of Patient Interactive Systems on the Management of Pain in an Inpatient Hospital Setting: A Systematic Review - Aldekhyyel, Raniah N.; Bakker, Caitlin J.; Pitt, Michael B.; Melton, Genevieve B. (Applied Clinical Informatics, 2019)
Background While some published literature exists on the use of interactive patient care systems, the effectiveness of these systems on the management of pain is unclear. To fill this gap in knowledge, we aimed to understand the impact and outcomes of pain management patient interactive systems in an inpatient setting.Methods A systematic literature review was conducted across seven databases, and results were independently screened by two researchers. To extract relevant data, critical appraisal forms were developed and each paper was examined by two experts. Information included patient interactive system category, patient population and number of participants/samples, experiment type, and specific outcome measures.Results Out of 58 full-text articles assessed for eligibility, 18 were eligible and included in the final qualitative synthesis. Overall, there were two main types of pain management interactive systems within the inpatient setting (standalone systems and integrated platform systems). While systems were diverse especially for integrated platforms, most reported systems were entertainment distraction systems. Reports examined a variety of outcome measures, including changes in patient-reported pain levels, patient engagement, user satisfaction, changes in clinical workflow, and changes in documentation. In the 13 systems measuring pain scores, 12 demonstrated a positive impact on pain level scores.Conclusion Pain management systems appear to be effective in lowering patient level scores, but research comparing the effectiveness and efficacy of one type of interactive system versus another in the management of pain is needed. While not conclusive, pain management systems integrated with other technology platforms show potentially promising effects with improving patient communication, education, and self-reporting.
Keywords: pain management; medical informatics applications; patient participation; outcome assessment